Exploring Circular Economy principles in the clothing manufacturing industry driven by fast fashion: Stakeholder Perspectives and Policy Implications in Cape Town, South Africa - Mukansi, Delian (Stellenbosch : Stellenbosch University, 2026)
Thesis (MPhil)--Stellenbosch University, 2026.